Effects of nutrients and water level on Phalaris arundinacea growth - Káplová, Miroslava (Jihočeská univerzita, 2011)
This thesis is an extension of my Bc. thesis. Based upon previously conducted research in a wet grassland, Mokré Louky, near Třeboň, Czech Republic, a mesocosm experiment was designed for investigating the effect of two nutrient regimes (non fertilized / fertilized) and three flooding regimes (saturated / spring flood / flooded) on Carex acuta and Phalaris arundinacea plants to determine the effect of management type for restoring a more diverse wet meadows system.
Effects of nutrients and water level on Phalaris arundinacea growth
Keywords: Phalaris arundinacea; Carex acuta; biomass; water level; nutrients; wet meadow; mesocosm; Phalaris arundinacea; Carex acuta; biomass; water level; nutrients; wet meadow; mesocosm